2015
DOI: 10.18632/oncotarget.4656
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule inhibitors of Late SV40 Factor (LSF) abrogate hepatocellular carcinoma (HCC): Evaluation using an endogenous HCC model

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 29 publications
7
43
1
Order By: Relevance
“…; Rajasekaran et al . ). However, the expression level of TFCP2 is decreased in melanoma, and up‐regulated TFCP2 suppresses melanoma cell growth and increases the percentage of G1 phase cells (Goto et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Rajasekaran et al . ). However, the expression level of TFCP2 is decreased in melanoma, and up‐regulated TFCP2 suppresses melanoma cell growth and increases the percentage of G1 phase cells (Goto et al .…”
Section: Discussionmentioning
confidence: 97%
“…Overexpressed TFCP2 functions as an oncogenic role in HCC pathogenesis. Inhibition of TFCP2 abrogates HCC cell growth and metastasis in vivo and in vitro (Santhekadur et al 2012;Rajasekaran et al 2015). However, the expression level of TFCP2 is decreased in melanoma, and up-regulated TFCP2 suppresses melanoma cell growth and increases the percentage of G1 phase cells (Goto et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fluorescent staining of synchronized cells for DNA and tubulin demonstrated that when control cells completed mitosis and re-entered G1, FQI-treated cells generally remained in mitosis with condensed but unaligned DNA (17). In order to elucidate the basis for these FQI1mediated mitotic defects and their consequences in greater detail, and over a range of FQI1 concentrations, we synchronized HeLa cells, which demonstrate the same phenotype, with a double thymidine block (Fig.…”
Section: Chemical Inhibition Of Lsf Induces Mitotic Defectsmentioning
confidence: 99%
“…Phenotypically, FQIs inhibit growth of hepatocellular carcinoma cells in vitro. They also inhibit hepatocellular carcinoma tumor growth in vivo in multiple mouse models, including a mouse endogenous liver tumor model (17). In all cases, inhibition of tumor growth occurred in the absence of toxicity, as assessed by liver injury markers, histopathology of tissues with rapid cell turnover, or blood cell counts (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation